2011
DOI: 10.1371/journal.pone.0021530
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Coexistence of Rotifer Cryptic Species

Abstract: Despite their high morphological similarity, cryptic species often coexist in aquatic habitats presenting a challenge in the framework of niche differentiation theory and coexistence mechanisms. Here we use a rotifer species complex inhabiting highly unpredictable and fluctuating salt lakes to gain insights into the mechanisms involved in stable coexistence in cryptic species. We combined molecular barcoding surveys of planktonic populations and paleogenetic analysis of diapausing eggs to reconstruct the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 66 publications
4
58
0
Order By: Relevance
“…Our second aim is to present a study of the evolutionary relationships among the species in the complex for a comparative analysis exploring the phylogenetic signal of biological traits and correlations among species-specific traits of the different species. The B. plicatilis species complex is by far the most extensively studied group of rotifers, and these animals have been used to investigate a wide variety of phenomena including ecological interactions (CirosPérez et al, 2001b(CirosPérez et al, , 2004(CirosPérez et al, , 2015Montero-Pau et al, 2011;Gabaldon et al, 2015), toxicology (Serrano et al, 1986;Snell & Persoone, 1989;Dahms et al, 2011), osmoregulation (Lowe et al, 2005), local adaptation (Campillo et al, 2009;Alcántara-Rodrí-guez et al, 2012), the evolution of sex , phylogeography Mills et al, 2007), ageing (Snell et al, 2015), and evolutionary processes (Stelzer et al, 2011;Fontaneto et al, 2012;Tang et al, 2014a). In addition, due to the ease and low cost of producing highly dense cultures of these rotifers, members of this species complex have been widely used in aquaculture as a source of live feed for larval crustaceans and fishes (Fukusho, 1983;Watanabe et al, 1983;Lubzens & Zmora, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our second aim is to present a study of the evolutionary relationships among the species in the complex for a comparative analysis exploring the phylogenetic signal of biological traits and correlations among species-specific traits of the different species. The B. plicatilis species complex is by far the most extensively studied group of rotifers, and these animals have been used to investigate a wide variety of phenomena including ecological interactions (CirosPérez et al, 2001b(CirosPérez et al, , 2004(CirosPérez et al, , 2015Montero-Pau et al, 2011;Gabaldon et al, 2015), toxicology (Serrano et al, 1986;Snell & Persoone, 1989;Dahms et al, 2011), osmoregulation (Lowe et al, 2005), local adaptation (Campillo et al, 2009;Alcántara-Rodrí-guez et al, 2012), the evolution of sex , phylogeography Mills et al, 2007), ageing (Snell et al, 2015), and evolutionary processes (Stelzer et al, 2011;Fontaneto et al, 2012;Tang et al, 2014a). In addition, due to the ease and low cost of producing highly dense cultures of these rotifers, members of this species complex have been widely used in aquaculture as a source of live feed for larval crustaceans and fishes (Fukusho, 1983;Watanabe et al, 1983;Lubzens & Zmora, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular techniques have shown that the former taxon B. plicatilis is actually a complex of fifteen cryptic species (Mills et al, 2017). Four species from this complex co-exist in the shallow ponds of the Mediterranean coast of Spain (Gomez et al, 1995;Ortells et al, 2003;Montero-Pau et al, 2011). Recently, three of them, B. plicatilis sensu stricto Müller, 1786, B. ibericus Ciros-Pérez, Serra, 2001 andB.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses about ecological niche differentiation between cryptic species are usually based on often limited information about geographical distributions (Ortells et al, 2003;Rissler and Apodaca, 2007). Abiotic niche differentiation has already been invoked as a likely explanation for the coexistence of cryptic species in e.g., rotifers, sea urchins and nematodes (Montero-Pau et al, 2011;Ortells et al, 2003;Palumbi and Metz, 1991;Van Campenhout et al, 2014).…”
Section: Introductionmentioning
confidence: 99%